Common Glomerular Diseases in Adult Jordanians: A Single-Center Experience - Ahmed Sheyyab; Mohammad Al-thnaibat; Aseel A. Zghayer; Jafar Alsheyyab; Radi Hamed (International Journal of Nephrology)
The pattern of glomerular diseases has been reported previously with contradictory results. Our primary objective is to assess the relative frequencies of glomerular disease in adult Jordanians and compare it with other institutes. A secondary objective is to assess the contribution of environmental factors, in an industrial city Zarqa, to kidney disease patterns. Methods. A retrospective study was conducted at a referral hospital center in the central region of Jordan. Assessment of native kidney biopsies, pathological reports, and the patients’ characteristics were obtained from electronic medical records. Results. Our study assessed a total of 178 biopsies, of which 106 patients were included achieving the age criterion for adults. The mean age of our patient was 34 ± 12.7. The number of females (53.7%) was slightly more than males (46.3%). The average creatinine at presentation was 198 umol/L. Almost half of the patients had mild renal impairment (50.9%), while the remaining were divided between moderate (26.1%) and severe (27.3%). The indications of kidney biopsy were proteinuria (11.3%), proteinuria (54.7%), and unexplained renal impairment (34%). The leading common glomerular diseases were represented as a group with a relative frequency ranging between 11% and 13%. Both IgA nephropathy (13.2%) and lupus nephritis (12.2%) were the top conditions causing the nephritic syndrome, while focal segmental glomerulosclerosis (12.2%) and minimal change disease (11.3%) were the conditions leading to nephrotic syndrome. Our secondary analysis showed nonstatistically significantly higher glomerular filtration rates in the city of Zarqa, when compared to Amman (median 94 and 54, respectively, U = 469.5, r = 0.08, p=0.491). Additionally, Zarqa had higher frequency rates of interstitial/tubular nephritis (χ2(1) = 1.17, p=0.279, Cramér’s V = 0.13. Conclusion. Common glomerular diseases, as reported internationally, were common among Jordanian adults.